2007
DOI: 10.1007/s00134-007-0719-7
|View full text |Cite
|
Sign up to set email alerts
|

Enoxaparin vs. unfractionated heparin for anticoagulation during continuous veno-venous hemofiltration: a randomized controlled crossover study

Abstract: Enoxaparin can be safely used for anticoagulation during CVVH resulting in higher filter lifespan compared with unfractionated heparin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
44
1
3

Year Published

2010
2010
2020
2020

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 85 publications
(50 citation statements)
references
References 38 publications
2
44
1
3
Order By: Relevance
“…No major bleeding occurred, but 26% of the patients in the enoxaparin group had minor bleeding episodes. This finding differs from the report by Reeves et al 30 and by Joannidis et al 35 who found no difference in the prevalence of hemorrhagic complications between the two methods of anticoagulation.…”
Section: Enoxaparin Vs Unfractioned Heparin In Cvvhd 325contrasting
confidence: 98%
See 4 more Smart Citations
“…No major bleeding occurred, but 26% of the patients in the enoxaparin group had minor bleeding episodes. This finding differs from the report by Reeves et al 30 and by Joannidis et al 35 who found no difference in the prevalence of hemorrhagic complications between the two methods of anticoagulation.…”
Section: Enoxaparin Vs Unfractioned Heparin In Cvvhd 325contrasting
confidence: 98%
“…Reeves et al 30 compared dalteparin with UFH in patients submitted to continuous venovenous hemodiafiltration, reporting a filter life span of 46.8 versus 51.7 hours for dalteparin and UFH, respectively, which is very similar to what was found in this study. In another study, 35 enoxaparin was associated with a longer filter life span as compared to UFH (30.6 ± 25.3 vs. 21.7 ± 16.9 hours, p = 0.017).…”
Section: Enoxaparin Vs Unfractioned Heparin In Cvvhd 325mentioning
confidence: 92%
See 3 more Smart Citations